Pengaruh Return on Asset (ROA), Return on Equity (ROE) dan Ukuran Perusahaan Terhadap Corporate Social Responsibility Disclosure - Kartini, Puti Tri; Maiyarni, Reka; Tiswiyanti, Wiwik (Jurnal Riset Akuntansi dan Keuangan, 2019)
Abstract. The purpose of this research isto determine the effect ofReturn On Asset (ROA), Return In Equity (ROE) and firm size towards Corporate Social Responsibility Disclosure. This research use companies listed on the Indonesian Stock Exchange (IDX) and Stock Exchange of Thailand (SET) period 2011 – 2017. Sampling method used in this research was purposive sampling.Samples collected in this research are 21 companies consists of 13 Indonesian companies and 8 Thailand companies. The method of analysis in this research is multiple regression analysis with technique analysis descriptive statistics. The result of hypothesis as follows. First, Return On Asset (ROA), Return On Equity (ROE) and firm size in simultan has an effect on Corporate Social Responsibility Disclosure in BEI and in SET. Second, Return On Asset (ROA) has an effect an effect on Corporate Social Responsibility Disclosure in BEI. Third, Return On Asset (ROA) has an effect an effect on Corporate Social Responsibility Disclosure in SET. Fourth, Return On Equity (ROE) has an effect an effect on Corporate Social Responsibility Disclosure in BEI. Fifth, Return On Equity (ROE) has an effect an effect on Corporate Social Responsibility Disclosure in SET . Sixth, firm size has no an effect an effect on Corporate Social Responsibility Disclosure in BEI. Seventh, firm size has no  an effect an effect on Corporate Social Responsibility Disclosure in SET. Keywords. Corporate Social Responsibility Disclosure; ROA; ROE and Firm Size.Abstrak. Tujuan Penelitian ini adalah untuk mengetahui pengaruh Return On Asset (ROA), Return On Equity (ROE) dan ukuran perusahaan terhadap Corporate Social Responsibility Disclosure.Penelitian ini menggunakan perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) dan  Stock Exchange Of Thailand (SET) periode 2011 – 2017. Teknik sampling yang digunakan adalah purposive sampling. Sampel yang digunakan dalam penelitian ini berjumlah 21 perusahaan terdiri dari 13 perusahaan Indonesia dan 8 perusahaan Thailand. Teknik analisis data dalam penelitian ini adalah analisis regresi linear berganda. Hasil pengujian hipotesis sebagai berikut. Pertama, Return On Asset (ROA), Return On Equity (ROE) dan ukuran perusahaan secara simultan berpengaruh terhadap Corporate Social Responsibility Disclosure pada perusahaan di BEI dan SET. Kedua, Return On Asset (ROA) berpengaruh terhadap Corporate Social Responsibility Disclosure pada perusahaan di BEI.  Ketiga, Return On Asset (ROA) berpengaruh terhadap Corporate Social Responsibility Disclosure pada perusahaan di SET. Keempat, Return On Equity (ROE) berpengaruh terhadap Corporate Social Responsibility Disclosure pada perusahaan di BEI. Kelima, Return On Equity (ROE) berpengaruh terhadap Corporate Social Responsibility Disclosure pada perusahaan di SET.  Keenam, ukuran perusahaan tidak berpengaruh terhadap Corporate Social Responsibility Disclosure pada perusahaan di BEI. Ketujuh, ukuran perusahaan berpengaruh terhadap Corporate Social Responsibility Disclosure pada perusahaan di SET.Kata kunci.  Corporate Social Responsibility Disclosure; ROA; ROE dan Ukuran Perusahaan.